2009
DOI: 10.4054/mpidr-wp-2009-010
|View full text |Cite
|
Sign up to set email alerts
|

Against all odds: fathers’ use of parental leave in Germany

Abstract: This paper investigates fathers' usage of parental leave in Germany based on data from the microcenses 1999-2005. We consider two competing hypotheses. On the one hand, we argue that value change is a driving force behind fathers' engagement in parenting activities. We assume that the 'new father' can more often be found among highly educated and urban men who are believed to be the forerunners in terms of new values and ideas. We contrast this hypothesis with the assumption that economic factors are the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 33 publications
1
28
0
4
Order By: Relevance
“…Individual/couple decisions. Intra-family negotiations regarding the allocation of time at work and household activities have been studied (Geisler and Kreyenfeld, 2011). Hence, in this axis we analyse discourses about how they cope with decision making and how hypotheses of individualization (Beck, 1986) may have an effect on their justification.…”
Section: Discussionmentioning
confidence: 99%
“…Individual/couple decisions. Intra-family negotiations regarding the allocation of time at work and household activities have been studied (Geisler and Kreyenfeld, 2011). Hence, in this axis we analyse discourses about how they cope with decision making and how hypotheses of individualization (Beck, 1986) may have an effect on their justification.…”
Section: Discussionmentioning
confidence: 99%
“…Fathers are more likely to take parental leave when their partners have more negotiating power in the relationship. For example, Geisler and Kreyenfeld (2011) find that German fathers with partners who are more educated or older are more likely to take parental leave than those with less educated, younger partners. In Sweden, a discourse of shared parental leave is starting to replace the more traditional norm of women caring for young children (Almqvist, Sandberg, and Dahlgren 2011).…”
Section: Partners and Decisions About Parental Leavementioning
confidence: 99%
“…For example, British men whose employers provide additional compensation, often for the second week of paternity leave, are more likely to take that extra time off (Hobson, Lewis, and Siim 2002). More stable employment increases men’s likelihood of taking parental leave (Geisler and Kreyenfeld 2011).…”
Section: Workplace Culture and Decisions About Parental Leavementioning
confidence: 99%
“…Evidence from other countries suggests high remuneration and ‘use-it-or-lose-it’ policies are the most effective in promoting fathers’ take-up of leave (Deven and Moss, 2002). A considerable body of research has also found that mothers’ higher earnings and fathers’ employers can impact on fathers’ take-up of leave (Bygren and Duvander, 2006; Geisler and Kreyenfeld, 2011; Brandth and Kvande, 2002; Haas et al , 2002; Reich, 2011). Fathers’ gender egalitarian ideology and support for leave also promotes uptake (Lammi-Taskula, 2008).…”
Section: What Is Known About Fathers’ Leave In the Uk?mentioning
confidence: 99%
“…The introduction of new policies in family and work reconciliation, such as Shared Parental Leave, enables individuals to imagine and perform new or different family practices. Previous studies have suggested that fathers’ probability of taking leave increases significantly if they have an individualised and non-transferable paid leave entitlement (O'Brien, 2009; Reich, 2011; Geisler and Kreyenfeld, 2011). We investigate whether a hypothetical situation, with an individualised leave entitlement of a similar duration for fathers to that which is currently available for mothers, would increase take-up intentions in the UK.…”
Section: Theoretical Framework For Investigating Leave-taking Plans Imentioning
confidence: 99%